Fulminant viral myocarditis treated by interferon-beta in a child. (December 2017) - Tahhan, Nabil; Fesseau, Rose; Berthomieu, Lionel; Hadeed, Khaled; Cuttone, Fabio; Dulac, Yves
Abstract: The fulminant viral myocarditis is associated to a high risk of mortality and heart transplantation in children. Anti-inflammatories and intravenous gamma globulin are used in the majority of studies but the outcome is not always favorable. In this case, we suggest an important role for antiviral therapy in children's fulminant myocarditis.